2018
DOI: 10.1007/s12311-018-0989-3
|View full text |Cite
|
Sign up to set email alerts
|

Neocerebellar Crus I Abnormalities Associated with a Speech and Language Disorder Due to a Mutation in FOXP2

Abstract: Bilateral volume reduction in the caudate nucleus has been established as a prominent brain abnormality associated with a FOXP2 mutation in affected members of the ‘KE family’, who present with developmental orofacial and verbal dyspraxia in conjunction with pervasive language deficits. Despite the gene’s early and prominent expression in the cerebellum and the evidence for reciprocal cerebellum-basal ganglia connectivity, very little is known about cerebellar abnormalities in affected K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…FOXP2 is expressed in mouse and human developing cerebellum and it has been previously implicated in speech and language disorders (31,32). It might be crucial for Purkinje cell development, as it is specifically expressed in those cells, and thus play a relevant role in vocal communication (28)(29)(30). Our searches in recent neurodevelopmental expression databases confirmed that FOXP2 expression in developing human brain is highest in cerebellum, around 12 pcw.…”
Section: Discussionsupporting
confidence: 69%
“…FOXP2 is expressed in mouse and human developing cerebellum and it has been previously implicated in speech and language disorders (31,32). It might be crucial for Purkinje cell development, as it is specifically expressed in those cells, and thus play a relevant role in vocal communication (28)(29)(30). Our searches in recent neurodevelopmental expression databases confirmed that FOXP2 expression in developing human brain is highest in cerebellum, around 12 pcw.…”
Section: Discussionsupporting
confidence: 69%
“…Positron emission tomography (PET) and functional MRI (fMRI) studies of the KE family have shown differential activation of cortical, basal ganglia, and cerebellar regions during word repetition, nonword repetition, silent verb generation, and spoken verb generation (Argyropoulos et al, 2018;Liegeois et al, 2003;Liegeois, Morgan, Connelly, & Vargha-Khadem, 2011;Vargha-Khadem et al, 1998; Figure 5b). Many under-or overactive brain regions in affected KE members also showed gray matter alterations in the structural MRI studies, including the inferior frontal gyrus, sensory and motor cortices, temporal gyri and pole, caudate nucleus, and cerebellar lobule VIIa Crus I (Argyropoulos et al, 2018;Belton et al, 2003;Vargha-Khadem et al, 1998;. In addition, fMRI of patient A-II during nonword repetition showed underactivation of the inferior frontal gyrus, but no differences between A-II and controls survived multiple comparisons correction (Liegeois et al, 2016).…”
Section: Relevance To Motor Learning-related Circuitrymentioning
confidence: 99%
“…A structural magnetic resonance imaging (MRI) data set was collected from both affected and unaffected KE family members and analyzed using several approaches, some involving additional control subjects. Across two or more analyses, affected KE members showed unilateral or bilateral gray matter decreases in cortex (inferior frontal gyrus, precentral gyrus, supplementary motor area, temporal pole), caudate nucleus, and cerebellum (lobules VIIa Crus I and VIIb-VIIIb); they also showed gray matter increases in other cortical areas (Argyropoulos et al, 2018 Vargha-Khadem et al, 1998;Figure 5a). Beyond the KE family, a patient (A-II) with a de novo intragenic FOXP2 deletion showed volume reductions in the globus pallidus, caudate nucleus, thalamus, and hippocampus compared with 26 controls (Liegeois et al, 2016).…”
Section: Relevance To Motor Learning-related Circuitrymentioning
confidence: 99%
“…Large‐scale systematic genome‐wide association studies have identified significant associations of intronic FOXP2 SNPs with several traits, including attention‐deficit/hyperactivity disorder (ADHD) (Demontis et al , 2019 ) and risk‐taking behaviors (Clifton et al , 2018 ). Although rare disruptions in FOXP2 have been associated with changes in brain activity (Liégeois et al , 2003 ) and structure (Watkins et al , 2002 ; Liégeois et al , 2016 ; Argyropoulos et al , 2019 ), common variation could not be linked to task‐based neural activations on language tasks (Uddén et al , 2019 ) or neuroanatomical differences between individuals (Hoogman et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%